Sustainable Pollutant Removal through Integrated Biological, Physical, Electrochemical Treatment: Resource Recovery and LCA Study - Agus Suprapto; Prabang Setyono; Jatmiko Wahyudi; Sajidan - Sajidan (Universitas Diponegoro, 2026)
Vinasse from bioethanol distillation contains high levels of organic matter, suspended solids, color, sulfides, and acidity, requiring integrated treatment beyond biological methods. This study tested a sequential system comprising anaerobic digestion, aerobic oxidation, sedimentation, and electrochemical oxidation using a Ti/RuO2 anode and stainless-steel cathode at different NaCl concentrations. The system reduced pollutants in 10% diluted vinasse, lowering COD, BOD, and TSS by 97.9 %, 99%, and 93.6%, respectively, eliminating sulfide, and increasing pH to 8.2. The electrochemical step polished water by generating hydroxyl radicals and reactive chlorine species. Six grams per liter of NaCl provided optimal water quality, with high color removal, turbidity reduction, sulfide removal, and pH stabilization. The GWP of the four resource-recovery techniques was assessed in a life cycle study. Sludge and biogas recovery produced the least climatic impact, according to Monte Carlo statistical analysis, which revealed GWP emissions of 0.842–1.125 kg CO2 eq/kg treated water across four suggested scenarios with a ≤3% coefficient of variation and a tiny standard error of the mean. Overall, this system combines pollutant removal, water recovery, sludge valorization, and environmental impact assessment to provide an efficient circular method for vinasse treatment